2017
DOI: 10.1534/g3.117.300260
|View full text |Cite
|
Sign up to set email alerts
|

APC/CFZR-1 Controls SAS-5 Levels To Regulate Centrosome Duplication inCaenorhabditis elegans

Abstract: As the primary microtubule-organizing center, centrosomes play a key role in establishing mitotic bipolar spindles that secure correct transmission of genomic content. For the fidelity of cell division, centrosome number must be strictly controlled by duplicating only once per cell cycle. Proper levels of centrosome proteins are shown to be critical for normal centrosome number and function. Overexpressing core centrosome factors leads to extra centrosomes, while depleting these factors results in centrosome d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…At anaphase, the ZYG-1 DB3(2A) mutation leads to elevated centrosomal SAS-5 (1.26±0.39 fold; mean±s.d.) compared to WT controls (1.00 ±0.27), which is nearly equivalent to the increase in SAS-5 KEN(3A) mutants (1.26±0.37 fold) where APC/C FZR-1 -mediated degradation of SAS-5 is blocked (Medley et al, 2017a). However, centrosomal SAS-5 levels are decreased in ZYG-1 DB2(2A) mutants (0.70±0.19 fold).…”
Section: Zyg-1 Contains Putative D-box Motifsmentioning
confidence: 79%
See 3 more Smart Citations
“…At anaphase, the ZYG-1 DB3(2A) mutation leads to elevated centrosomal SAS-5 (1.26±0.39 fold; mean±s.d.) compared to WT controls (1.00 ±0.27), which is nearly equivalent to the increase in SAS-5 KEN(3A) mutants (1.26±0.37 fold) where APC/C FZR-1 -mediated degradation of SAS-5 is blocked (Medley et al, 2017a). However, centrosomal SAS-5 levels are decreased in ZYG-1 DB2(2A) mutants (0.70±0.19 fold).…”
Section: Zyg-1 Contains Putative D-box Motifsmentioning
confidence: 79%
“…Prior study has identified SAS-5 as an APC/C FZR-1 substrate, and implicated APC/C FZR-1 as targeting additional centrosome regulators in C. elegans (Medley et al, 2017a). FZR-1 was identified as a genetic suppressor of ZYG-1 since loss of FZR-1 restores embryonic viability and centrosome duplication to zyg-1(it25) mutants (Kemp et al, 2007;Medley et al, 2017a). Given the strong genetic interaction between zyg-1 and fzr-1, a compelling possibility is that ZYG-1 might be an APC/C FZR-1 substrate.…”
Section: Results and Discussion Loss Of Fzr-1 Leads To Elevated Centr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, negative regulation of SAS-5 levels also is important for the control of centriole duplication. The same screen that led to the identification of a role for PP1 in limiting ZYG-1 levels also recovered two loss-of-function alleles of the FZR-1/Cdh1 subunit of the anaphase promoting complex/cyclosome (APC/C) E3 ligase as suppressors of a TS zyg-1 centriole duplication defect (Medley et al 2017a). Further investigation showed that FZR-1/Cdh1 and other APC/C subunits are required to limit SAS-5 levels ( Figure 3B).…”
Section: Limiting Centriole Duplication By Controlling the Levels Of mentioning
confidence: 91%